Platelet count to splenic diameter ratio and other noninvasive markers as predictors of esophageal varices in patients with liver cirrhosis - Jamil, Zubia; Malik, Maryam; Durrani, Asghar Aurangzeb (Turkish Journal of Gastroenterology, 2017)
Abstract Background/Aims: Endoscopy as a screening modality for esophageal varices is becoming difficult because of its invasiveness, cost, and increased burden of liver cirrhosis. This study aims to determine the diagnostic accuracy of simple and noninvasive markers in detecting esophageal varices. Materials and Methods: Four variables (platelet count, portal vein diameter, splenic diameter, and ratio of platelet count to splenic diameter PC/SD] ratio) were studied in 150 cirrhotic patients. Endoscopy was performed to detect esophageal varices in the patients. The diagnostic accuracy of these variables was determined by obtaining area under the receiver operating characteristic (ROC) curve (AUC). The cutoff value of each variable and its sensitivity, specificity, positive and negative predictive values, and positive and negative likelihood ratios were obtained using the Youden index. Pairwise comparison of these variables was performed using the Hanley and McNeil method to determine the most reliable screening tool among them. Results: The PC/SD ratio was the most reliable indicator for the presence of varices: AUC=0.9 (p Conclusion: The PC/SD ratio is found to be the most reliable marker to prognosticate esophageal varices. It is easy to obtain and can be used with other markers to identify the high-risk patients for developing esophageal varices. It will definitely reduce the need for endoscopy as screening purposes and lower the medical expenditures. Cite this article as: Jamil Z, Malik M, Durrani AA. Platelet count to splenic diameter ratio and other noninvasive markers as predictors of esophageal varices in patients with liver cirrhosis. Turk J Gastroenterol 2017; 28: 347-52